Potential role of medicinal plants for anti-atherosclerosis activity - Muhammad Imran Qadir; Ayesha Manzoor; Muhammad Sajid Hamid Akash (Bangladesh Pharmacological Society, 2018)
Atherosclerosis may lead to the death of a number of people. In case of atherosclerosis, stiffness of arteries of the heart is caused by the excess deposition of lipids in the coronary arteries. The mentioned condition produces atherosclerotic plaques. When these plaques are burst then clots of blood are formed that cause coronary issues. To overcome this severe disease, extracts of many medicinal plants or spices like garlic, ginger and onion, and many others that are mentioned in this review are used to treat atherosclerosis.